Improving MSME perfomance through competences and entrepreneurial characteristics - Rr. Lulus Prapti Nugroho Setiasih Surjanti; Edy Mulyantomo; Dian Triyani; Emaya Kurniawati (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of human resource competence, management competence, and entrepreneurial competence on the performance of Micro, Small and Medium Enterprises (MSMEs), moderated by entrepreneurial characteristics. Methodology: The research was conducted on 95 MSME actors from the